OP54 Alcohol consumption in pregnancy and childhood hearing and neurodevelopmental problems in the UK: analysis from the millennium cohort study. (September 2018) - Straatmann, VS; Taylor-Robinson, DC; Bergh, EH; Fleming, KM
Abstract : Background: Fetal Alcohol Spectrum Disorders (FASD) is the leading preventable cause of disability in children in the UK. Identification and diagnosis of FASD is poor, with many children receiving diagnoses of other neurodevelopmental deficit (including Attention Deficit Hyperactivity Disorder -ADHD), but no FASD diagnosis. FASD is associated with a large number of comorbid conditions, including an 80-fold increased risk of sensorineural hearing loss. Using a contemporary UK birth cohort we examined the association between maternal alcohol consumption in pregnancy, hearing problems at age 3 and later ADHD. Methods: Analysis of the UK Millennium Cohort Study (MCS), based on 9179 children participating in 3 survey sweeps (9 months, 3, 7 years old). The main outcome was parental-reported hearing problems, at age 3. We also examined self-reported diagnosis of ADHD at age 7. Incident rate ratios (IRRs; 95% confidence intervals [CI]) were estimated using Poisson regression, according to maternal drinking in pregnancy in units per week (categorised as none, 1–7, 8–14 and 15 or more) adjusted for measures of childhood socioeconomic conditions. Analyses were conducted using Stata/SE with svy commands to account for the sampling design and attrition. Results: At age 3, 1328 children (14.4%) had reported a hearing problem with the most common of these being otitis media and unspecified hearing loss. Children of mothers who reported drinking 15 or more units per week of alcohol in pregnancy were twice as likely to have hearing problems compared to mothers who reported never drinking in pregnancy (aIRR1.9(95% CI[1.07, 3.39])). Risk of ADHD diagnosis at age 7 was also elevated in children of mothers who drank 15 or more units per week though this was not statistically significant at the 5% level (aIRR2.79(95% CI[0.91, 8.57])). Children with hearing problems at age 3 were 3.5 times more likely to have a diagnosis of ADHD at age 7 (aIRR3.49(95% CI[1.92, 6.32])). Conclusion: In a representative UK child cohort we found a significant prevalence of parental reported hearing problems at age 3 which was associated with high maternal alcohol consumption in pregnancy. Hearing problems were associated with a higher risk of ADHD. Self-reported data of both alcohol consumption and hearing problems is a limitation of this study. Maternal alcohol consumption is rarely captured in child health records in the UK making follow-up of potentially exposed children difficult. Further investigation in children with hearing loss could lead to earlier diagnosis of neurodevelopmental conditions, including FASD, and provide opportunities to intervene and improve outcomes.